2011
DOI: 10.1007/s00438-011-0645-9
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-specific ligation detection reaction (msLDR): a new approach for multiplex evaluation of methylation patterns

Abstract: A new sensitive method for multiplex gene-specific methylation analysis was developed using a ligation-based approach combined with a TaqMan-based detection and readout employing universal reporter probes. The approach, termed methylation-specific Ligation Detection Reaction (msLDR), was applied to test 16 loci in 8 different colorectal cancer cells in parallel. These loci encode immune regulatory genes involved in T-cell and natural killer cell activation, whose silencing is associated with the development or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The HLA-A locus also has a miR-148a binding site in its 3′UTR, but unlike HLA-C, the seed region in the HLA-A locus is fixed for the form that is inhibited by miR-148a (7,18), so differential miR-148a binding cannot account for variation in HLA-A expression levels. Several studies have identified DNA methylation as an epigenetic mechanism responsible for varied expression levels of genes located within the MHC region (11)(12)(13)(19)(20)(21)(22). Variation in HLA-A methylation levels may play a role in certain cancers (10)(11)(12)(13), but these studies have not addressed whether differential, allelic lineage-specific DNA methylation patterns occur at the locus and whether they affect HLA-A expression levels in a lineage-specific manner.…”
Section: Introductionmentioning
confidence: 99%
“…The HLA-A locus also has a miR-148a binding site in its 3′UTR, but unlike HLA-C, the seed region in the HLA-A locus is fixed for the form that is inhibited by miR-148a (7,18), so differential miR-148a binding cannot account for variation in HLA-A expression levels. Several studies have identified DNA methylation as an epigenetic mechanism responsible for varied expression levels of genes located within the MHC region (11)(12)(13)(19)(20)(21)(22). Variation in HLA-A methylation levels may play a role in certain cancers (10)(11)(12)(13), but these studies have not addressed whether differential, allelic lineage-specific DNA methylation patterns occur at the locus and whether they affect HLA-A expression levels in a lineage-specific manner.…”
Section: Introductionmentioning
confidence: 99%
“…Ligases have been used to amplify single-DNA base changes with the ligase chain reaction (LCR) and ligase detection reaction (LDR) assays (25,26 ). Both LCR and LDR have been used to detect methylation at single CpGs and have been coupled to various readout platforms (14, 15, 26 -29 ), but the most common ap- Methylated sites (M, shaded circles) and unmethylated (U, open circles).…”
mentioning
confidence: 99%
“…48 Methylation of ULBP2 and ULBP3 has previously been reported in colon cancer cell lines. 35,49 However, we found that all the ligands analyzed (MICA, MICB, ULBP1, ULBP2 and ULBP3) were unmethylated and highly expressed in colon cancer cell lines. Moreover, analysis of the NKG2DL methylation status in colon cancer patients showed that both normal and tumor tissues from colon cancer patients were hypomethylated independently of the tumor stage.…”
Section: Discussionmentioning
confidence: 86%